Hubungan Pengetahuan Terhadap Sikap Ibu Hamil Tentang Pemanfaatan Buku KIA di Poskedes Desa Betung Bedarah Barat Tahun 2022 - Yulidar; mariany puspita subrata; Rt. Novita Wahyu Handayani (Universitas Adiwangsa Jambi, 2022)
Utilization of maternal and child health services is still constrained by the lack of knowledge and attitudes of mothers regarding the danger signs of pregnancy and other matters regarding pregnancy, childbirth, and children under 5 years of age regarding the use of the Maternal and Child Health (KIA) book. Most pregnant women think that the MCH handbook is only used for pregnancy records. The correct application of the Maternal and Child Health (MCH) book will have an impact on increasing maternal and family knowledge about maternal and child health, mobilizing and empowering the community to live healthy, increasing public access to quality health services and improving surveillance, monitoring and health information systems. Good knowledge will make mothers have a positive attitude towards the use of Maternal and Child Health (KIA) books. The purpose of this study was to examine the relationship between knowledge and attitudes of pregnant women regarding the use of MCH books in Betung Bedarah Barat Village, Tebo Regency, Jambi Province.This research method uses the interview method with descriptive analytic research type with chi square test to see the relationship between knowledge and attitudes of pregnant women about the use of MCH books.From the results of the study, it was found that knowledge of the attitudes of pregnant women about the use of MCH books was obtained with a p value of 0.009 with a 95% confidence degree (p <0.05) so that the conclusion was that there was a significant relationship between knowledge and attitudes of pregnant women about the use of MCH books at Poskesdes Desa Betung. West Blood in 2022.Based on research results show knowledge and attitudes have a relationship with pregnant women to find out the benefits of MCH books, as well as the need for periodic counseling because not all pregnant woman remember or know the benefits of MCH books.